Electromagnetic Compatibility for Device Design and System Integration - Gonschorek, Karl-Heinz; Vick, Ralf (Springer Berlin Heidelberg : Imprint: Springer, 2009)
The Electromagnetic Compatibility has become an increasingly essential factor for placing a product on the global, world wide market. Fulfilling emission limits and immunity requirements as well as handling apparently complex cases of incompatibility demands a deeper understanding of the physical interrelations and of Maxwell's theory. Based on the authors' experiences, the textbook provides some help in solving such interferential cases. It contains many illustrative examples and more than 80 exercises with solutions.